E-Module Behavior Counseling Practicum Based on Case Study - Indreswari, Henny; Fauzan, Lutfi; Probowati, Devy; Apriani, Rizka (Jurnal Kajian Bimbingan dan Konseling, 2023)
One of the mandatory courses for students majoring in guidance and counseling is a behavior counseling practicum. The purpose of this research is to develop the behavior counseling e-module based on case studies that can be applied to students of guidance and counseling. The research and development design used in this study is the ADDIE model. The instrument used is a module assessment scale. The assessors are experts in guidance and counseling, media, language, and prospective users. Index agreement result of the product by the guidance and counseling expert validator is 1 (very high), the media expert is 0.93 (very high), the language expert is 0.90 (very high), and the user assessment showed the mean score is 3.55 (very high in 4 scales). The developed product, e-module, has met the product acceptability criteria from various specified aspects.